(untitled) (Medical Forum Monthly, 2024)
Objectives: To analyze the factors associated with length of inpatient stay of individuals with stroke at a tertiary care rehabilitation hospital in Saudi Arabia. Study Design: Retrospective Cohort Study. Place and Duration of Study: This study was conducted at the Inpatient Department of Physical Medicine & Rehabilitation, King Fahad Medical City, Riyadh Saudi Arabia at King Fahad Medical City, Riyadh from June 2010 to June 2011. Materials and Methods: The rehabilitation data of sixty stroke patients discharged from inpatient stroke rehabilitation unit was collected retrospectively. Patients who were not able to complete their rehabilitation either due to death or discharge against medical advice, were excluded from the study. Patients who were difficult to be discharged or who were shifted to other medical service due to medical instability were not included in the study. Complex Statistical analysis was carried out using SPSS version 17. Results: Our study included 60 patients with 62% males and 38% females. Mean descriptive analysis for age, Length of stay in acute (LOSa), Length of stay in rehab (LOSr), Functional status at admission (FIMa) and Functional status at discharge (FIMd) are 63.4 years, 22.1 days, 48.8 days, 59.7 and 80.8 respectively. LOSr was more in hemorrhagic stroke patients. FIMd has a strongly positive correlation with FIMa and has a negative correlation with age and LOSa. LOSr has a negative correlation with FIMa and age. In a multivariate linear regression model the only significant variable was age. Conclusion: Earlier rehabilitation interventions during acute stroke care should be emphasized as it can not only improve the functional outcomes of patient during inpatient rehabilitation but also shorten the length of stay in rehabilitation unit.